THE EFFECTS OF COLLABORATIVE GAMES IN TEACHING ENGLISH LANGUAGE TO STUDENTS - Roldan Cabiles (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
The main objective of this study was to look into the effects of collaborative games in teaching English language to students based on the teacher-made instructional materials for Grade 9 students, administered in the experimental group. This study applied quasi-experimental design wherein two (2) sections of Grade 9 students were involved in the conduct of this study whereas one (1) section made use of the developed intervention (experimental) and the other section employed the lecture-discussion method (control). The pretest yielded that students did not meet expectations or have poor understanding of verbals and literary devices as the lesson objectives; therefore, contextualized collaborative games were made to improve their learning on the topics. Moreover, after the implementation of the intervention to the experimental group, it was found out that the developed instructional materials were effective and created learning improvement on students’ conceptual understanding regarding verbals and literary devices. Thus, the principles of a game-based type of activities or lessons can be an effective strategy in teaching English language specially to academically challenged learners.